Phytogenic Compounds for Enhancing Intestinal Barrier Function in Poultry–A Review - Latek, Urszula; Chłopecka, Magdalena; Karlik, Wojciech; Mendel, Marta (Planta Medica, 2021)
After the European Union ban of antibiotic growth promoters, works on different methods of improving gut health have intensified. The poultry industry is struggling with problems that were previously controlled by antibiotic growth promoters, therefore the search for optimal solutions continues. Simultaneously, there is also increasing social pressure to minimize the use of antibiotics and replace them with alternative feed additives. A variety of available alternatives is considered safe by consumers, among which phytogenics play a significant role. However, there are still some limitations that need to be considered. The most questionable are the issues related to bioavailability, metabolism of plant derivatives in birds, and the difficulty of standardizing commercial products. There is still a need for more evidence-based recommendations for the use of phytogenics in livestock. On the other hand, a positive influence of phytogenic compounds on the health of poultry has been previously described by many researchers and practical application of these compounds has auspicious perspectives in poultry production. Supplementation with phytogenic feed additives has been shown to protect birds from various environmental threats leading to impaired intestinal barrier function. Phytogenic feed additives have the potential to improve the overall structure of intestinal mucosa as well as gut barrier function on a molecular level. Recognition of the phytogenicsʼ effect on the components of the intestinal barrier may enable the selection of the most suitable ones to alleviate negative effects of different agents. This review aims to summarize current knowledge of the influence of various phytogenic constituents on the intestinal barrier and health of poultry.
Keywords: intestinal permeability; gut health; alternative feed additives; poultry; plant derivatives